Educating the more able student :What works and Why - Stephen, Martin; Warwick, Ian (sage Newdelhi, 2015)
"An unprecedented collaboration between leading names from the independent and state sectors, this thought-provoking book addresses the current crisis in education for the most able. Grounded in the classroom, the authors draw on their own first-hand experiences and international research to scrutinise techniques and practices from leading countries, exploring the more divisive issues that have damaged teaching worldwide. Demonstrating what works well in teaching the most able, and also what does not work, the book offers a radical solution, a stimulus to thought and a way forward for teachers, academics and all those with responsibility for ensuring high standards in education, including governments and members of regulatory authorities."--Back cover.
Keywords: Gifted children -- Education -- Education - Technique and Methods -- Techniques and renzulli approach, acceleration and compaction, Robinson center for young scholars, enrichment and add-in, out of class enrichment- internet and summer schools, Hungarian genius program, competitions and territory links, specialist schools and issue of selection, teacher training, resources and cluster approach, disadvantage, gender and ability as an illness -- Countries : PISA tables, UK, Finland and south Korea, Singapore and Hong Kong, Australia, USA -- Future directions : Proposal for UK, creativity, critical thinking and mindfulness; Gifted children